Recalibrating the New Thai Vernacular Architecture - Punpairoj, Poomchai (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The emergence of the new types of vernacular houses shows the evidence of change leaping from the popular image of the traditional Thai houses. The change is impacted from many factors including contemporary cultural needs. New vernaculars, which are found in the central Thailand, are the transforming Thai houses and the reproduction Thai houses. These two occurrences began since the 1960s (for the first type) and the 1990s (for the second type). The vernacular houses were surveyed in Pak Kran village and Bang Pahun area in Phra Nakhon Si Ayutthaya province during the 2000s. These new vernacular houses have developed from the traditional Thai house among other modern housing developments. However, there is lacking of awareness and understanding of the change. Most of the policies from Thai government, study courses and research topics have focused only on the image in the past. Accordingly, contemporary vernaculars tend to be disregarded. For recalibrating the new vernaculars in this paper, there are three main subjects: 1. the viewpoints on vernacular architectures both from local and international scholars; 2. the definitions and previous studies relating to vernaculars; and 3. the establishment of the new vernacular architectures, which closely relate to the traditional Thai house. This paper involves developing an understanding of vernaculars as well as providing ways to expand the scope of vernacular studies.